2021
DOI: 10.1002/med.21856
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the scaffold diversity of cyclin‐dependent kinase inhibitors and revisiting the clinical and preclinical pipeline

Abstract: Kinases have gained an important place in the list of vital therapeutic targets because of their overwhelming clinical success in the last two decades. Among various clinically validated kinases, the cyclin‐dependent kinases (CDK) are one of the extensively studied drug targets for clinical development. Food and Drug Administration has approved three CDK inhibitors for therapeutic use, and at least 27 inhibitors are under active clinical development. In the last decade, research and development in this area to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 272 publications
(515 reference statements)
0
15
0
Order By: Relevance
“…We investigated the chemical scaffolds of pan-CDK inhibitors in clinical trials and found that the most commonly used scaffolds include 5-hydroxy-4 H -chromen-4-one, 9 H -purin-6-amine, thiazol-2-amine, pyrimidin-2-amine, 1 H -pyrazole, pyrazolo­[1,5- a ]­pyrimidin-7-amine, and 1 H -pyrazol-4-amine, as depicted in Figure . These scaffolds are very important for binding CDKs because they provide atoms that can form critical hydrogen bonds with the hinge regions of CDKs …”
Section: Lessons From Cdk Drug Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated the chemical scaffolds of pan-CDK inhibitors in clinical trials and found that the most commonly used scaffolds include 5-hydroxy-4 H -chromen-4-one, 9 H -purin-6-amine, thiazol-2-amine, pyrimidin-2-amine, 1 H -pyrazole, pyrazolo­[1,5- a ]­pyrimidin-7-amine, and 1 H -pyrazol-4-amine, as depicted in Figure . These scaffolds are very important for binding CDKs because they provide atoms that can form critical hydrogen bonds with the hinge regions of CDKs …”
Section: Lessons From Cdk Drug Discoverymentioning
confidence: 99%
“…In 2021, the oral selective CDK7 inhibitor XL102 (structure undisclosed), developed by Exelixis, entered a phase I trial for multiple solid tumors, and patients are being recruited (NCT04726332). BCD-115 (24), a selective oral CDK8 inhibitor, entered a phase II trial for breast cancer treatment in 2017 (NCT03065010).…”
Section: Discovery and Development Of Cdk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK8 and its analogue CDK19 regulate distinct gene profiles, and both may need to be inhibited for the optimum therapeutic benefit [182]. Indeed, several CDK8/CDK19 inhibitors are in preclinical development, and one-BCD-115-has completed Phase I clinical trials (Trial identifier: NCT03065010), although the results have not yet been posted [198]. Recently, Ma et al reviewed the binding profiles of 24 CDK8 inhibitors and highlighted four methods of identifying new inhibitors, which may be more selective for CDK8 [199].…”
Section: Cdk8 and The Mediator Complexmentioning
confidence: 99%
“…Zhang et al 13 summarized the preclinical pharmacological and clinical effects of some pan-CDK inhibitors and selective CDK inhibitors. Bhurta et al 14 analyzed the scaffold diversity of CDK inhibitors. Łukasik et al 15 reviewed the representative ATP-competitive CDK inhibitors and allosteric inhibitors in active development.…”
Section: Introductionmentioning
confidence: 99%